Analysis of Hypokalemia as a Side Effect of Liposomal Amphotericin in Pediatric Patients. Issue 5 (May 2018) - Kobayashi, Ryoji; Keino, Dai; Hori, Daiki; Sano, Hirozumi; Suzuki, Daisuke; Kishimoto, Kenji; Kobayashi, Kunihiko
Abstract : Background: Liposomal amphotericin (L-AMB) is a widely used broad-spectrum antifungal drug. Although L-AMB demonstrates better safety compared with amphotericin, renal dysfunction and hypokalemia are well-known adverse effects of L-AMB. Method: We analyzed 56 episodes in 40 children and adolescents who received L-AMB therapy to determine risk factors of hypokalemia. Results: Hypokalemia (<3.0 mEq/L continuously for more than 2 episodes) was observed in 31 of 56 episodes (55.4%). The median onset of hypokalemia was at 10 days on L-AMB (range, 3–54 days), and the median cumulative dose of L-AMB at occurrence of hypokalemia was 25 mg/kg (range, 10–167.5 mg/kg). None of the patients with hypokalemia had solid tumors, and they had significantly higher estimated glomerular filtration rates than those with normokalemia ( P = 0.013). Seven of 25 (28.0%) patients in the normokalemia group and 1 of 31 (3.2%) patients in the hypokalemia group had eGFRs of <90 mL/min/1.73 m 2 ( P = 0.017). Conclusion: Although the reason for the association between estimated glomerular filtration rates and hypokalemia is unclear, assessing the estimated glomerular filtration rates before L-AMB administration may predict the development of hypokalemia.